PENGARUH MODEL PEMBELAJARAN CORE (CONNECTING, ORGANIZING, REFLECTING, EXTENDING) TERHADAP KEMAMPUAN PEMAHAMAN KONSEP DAN KEMAMPUAN PENALARAN MATEMATIKA SISWA SEKOLAH MENENGAH KEJURUAN - Bayu Putra Irawan (LP4MK STKIP PGRI Lubuklinggau, 2018)
The aims this study are to find out: (1) the influence of CORE learning approach toward the ability of comprehension concepts of students, and (2) the effect of using CORE learning approach the ability of intelectual activity in Mathematics of students. This study is pure types of experiment research which applied control group Pretest-postest. The data colection methods used thecnique test. The subjects of this research were all the first grade students of Departement of Administration office of SMK-S 5 Pembangunan Curup, Rejang Lebong, Bengkulu. Province, in the academic year 2014/2015. The sampel used in this research 27 students were in experiment class and 28 students were control class. Based on the result of analysis, it could be concluded that, (1) There are significant influnces of CORE learning toward students ability in understanding concept of mathematics. (2) There are significant influence of CORE learning approach the ability of intellectual activity in mathematics of students.